Constructing fair sports leagues schedules - Dirk Briskorn; Sigrid Knust (Universität Kiel, Institut für Betriebswirtschaftslehre, 2008)
A single round robin tournament (SRRT) consists of n teams and a set of periods. Matches between the teams have to be scheduled such that each team plays against each other team exactly once and each team plays at most once per period. In order to establish fairness among teams we consider a partition of the teams into strength groups. Then, the goal is to avoid that a team plays against extremely weak or extremely strong teams in consecutive periods. In this paper we pick up two concepts ensuring different degrees of fairness and adress several questions which remained open so far.
Keywords: 650; sports scheduling; round robin tournaments; fairness; strength groups; graphs; Sport; Scheduling-Verfahren; Graphentheorie; Gerechtigkeit; Theorie